The flattie spiders of the Selenops isopodus species group (Araneae: Selenopidae) with a review of Selenops records from Colombia - Crews, Sarah C.; Galvis, William; Torres, Richard A.; Gutiérrez-Estrada, Miguel A.; Sarmiento, Jessica; Esposito, Lauren A. (Zootaxa, 2021)
Here we examine the species of the Selenops isopodus species group: S. isopodus Mello-Leitão, 1941, S. arikok Crews, 2011, and S. curazao Alayón, 2001. We describe the female and male of S. bullerengue sp. nov. from Colombia and synonymize S. marilus Corronca, 1998a with S. isopodus, providing diagnoses and complete descriptions of both sexes of S. isopodus. Detailed images and a key to species in the group are provided. The distribution of all selenopid species in Colombia is reviewed using published records, museum specimens, and citizen science data from inaturalist.org.